The Effect of Mandatory Adoption Pressures of International Financial Reporting Standards (IFRS/IAS) on Irregular Auditing Practices: An analytical study of the opinions of a sample of academic and professional accountants in the Kurdistan Region of Iraq - Salwan Neamat Hanna; Serwan Kareem Essa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The research aims to determine the effect of mandatory (IFRS/IAS) standards adoption pressures on irregular auditing practices, considering that these standards impose multiple pressures on External Auditors working in the Iraqi Kurdistan Region when dealing with them and obligating them to adopt, through the research problem, which indicates that obligating economic units in the region to adopt (IFRS/IAS) standards in the absence of requirements for their application results in great pressures on the auditing profession, This leads to the External Auditors being subjected to Audit time pressures and Audit Fees pressures, which may lead the External Auditors to Engaging in irregular auditing practices. In order to reach this goal, the opinions of a sample of academic accountants (university lecturers) and professionals (external auditors) in the Iraqi Kurdistan Region were surveyed, who numbered (168) individuals, questionnaire forms were distributed, and the results were analyzed using The Statistical Package for Social Sciences (SPSS) program. The research reached a set of conclusions, the most important of which is that obligating economic units to adopt (IFRS/IAS) standards when the requirements for adopting these standards are not available creates pressures on the work of External Auditors, especially Audit time pressures and audit fees pressures and makes them engage in irregular auditing practices in response to those the pressures they are exposed to. The research suggested working to enhance the reputation of the auditing profession in the Iraqi Kurdistan Region, as it is the guarantor of the quality of financial reports issued by economic units, by imposing penalties and fines on all External auditors who are proven to practice dysfunctional behaviors and irregular practices, and do not abide by the ethics of the profession and they deviate from proper professional conduct and performance when performing audit assignments.